Dinamika Media Sosial TikTok dalam Membentuk Toleransi Antarbudaya: Tinjauan Literatur Era Digital - Adde, Exsan; Laksmono, Vidyardi; Dewi, Ramadhani Utami; Sari, Dwi Ulina; Julika, Mauly Arzak (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
The evolution of digital technology, particularly the TikTok platform, has transformed the landscape of intercultural communication into a global discursive space for the expression and negotiation of complex identities. This study critically analyzes TikTok's role in shaping intercultural tolerance by questioning the effectiveness of algorithms amidst the risks of information bias and stereotypes. The research method employed is a qualitative literature study with thematic analysis techniques applied to 12 selected scientific articles indexed in SINTA and Scopus (2020–2025). The results indicate that TikTok functions as a performative arena where users construct digital personas through stylization and code-mixing strategies to enhance intercultural sensitivity. However, this study asserts a contradiction in algorithmic mechanisms that potentially reinforce fragmented cultivation patterns and the dominance of specific cultures (digital imperialism). These findings identify that the platform's effectiveness in fostering substantive tolerance heavily relies on the synergy between users' critical media literacy and the development of inclusive content to minimize communication conflicts.